2001
DOI: 10.2337/diacare.24.9.1596
|View full text |Cite
|
Sign up to set email alerts
|

Stress Echocardiography for Risk Stratification of Diabetic Patients With Known or Suspected Coronary Artery Disease

Abstract: OBJECTIVE -Coronary artery disease (CAD) is a leading cause of mortality and morbidity in diabetic patients; therefore, their risk stratification is a relevant issue. Because exercise tolerance is frequently impaired in these patients, pharmacological stress echocardiography (SE) has been suggested as a valuable alternative. Our aim was to evaluate the prognostic value of this technique in diabetic patients with known or suspected CAD. RESEARCH DESIGN AND METHODS-A total of 259 consecutive diabetic patients un… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
24
0

Year Published

2001
2001
2011
2011

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 56 publications
(27 citation statements)
references
References 32 publications
3
24
0
Order By: Relevance
“…Quantification of ischemia using a wall-motion score index on DSE (with higher numbers reflecting increasingly abnormal wall motion at peak exercise) offered significant additional prognostic value for cardiac events ( 2 37 versus 18, PϽ0.05) and all-cause mortality ( 2 52 versus 43, PϽ0.05). Bigi et al 46 also assessed the value of pharmacological stress echocardiography for risk stratification of diabetic patients with known or suspected CAD. A total of 259 patients with DM underwent dobutamine (42%) or dipyridamole (58%) stress echocardiography and were followed up for a mean of 2 years for cardiac death and nonfatal MI.…”
Section: Prognostic Valuementioning
confidence: 99%
“…Quantification of ischemia using a wall-motion score index on DSE (with higher numbers reflecting increasingly abnormal wall motion at peak exercise) offered significant additional prognostic value for cardiac events ( 2 37 versus 18, PϽ0.05) and all-cause mortality ( 2 52 versus 43, PϽ0.05). Bigi et al 46 also assessed the value of pharmacological stress echocardiography for risk stratification of diabetic patients with known or suspected CAD. A total of 259 patients with DM underwent dobutamine (42%) or dipyridamole (58%) stress echocardiography and were followed up for a mean of 2 years for cardiac death and nonfatal MI.…”
Section: Prognostic Valuementioning
confidence: 99%
“…Conversely, Bates et al (16) reported that DSE was a powerful test for the prognostic stratification of 53 patients with juvenileonset insulin-dependent diabetes who were considered for kidney and/or pancreas transplantation. Recently, Bigi et al (22) studied 108 diabetic patients who were followed-up for 20 Ϯ 17 months after DSE and 151 diabetic patients who were followed-up for 33 Ϯ 26 months after dipyridamole stress test. Cox's model selected peak wall motion score index as the only significant independent predictor of cardiac events.…”
Section: Previous Studiesmentioning
confidence: 99%
“…Surprisingly, stress tests are positive in only 30% to 50% of patients with diabetes, even when symptoms compatible with coronary artery disease are present. 38,39 In those patients with positive stress tests, specificity is less than optimal. If coronary disease is documented by stress testing, patients must then agree to undergo coronary arteriography.…”
Section: What Can We Expect From Bari 2d?mentioning
confidence: 99%